THE EFFECT OF EDUCATION POLICY ON ACCESSIBILITY AND QUALITY OF LEARNING - Nurlena Nurlena; Sri Utami; Busnawir Busnawir (CV. ADIBA AISHA AMIRA, 2025)
Education policy plays a crucial role in determining the level of accessibility and quality of learning. This research highlights how inclusively and fairly designed policies can ensure equitable distribution of resources, thus providing equal opportunities for all students, including those in remote areas. In addition, policies that support teachers' professional development, as well as curriculum updates, contribute significantly to improving the effectiveness of the learning process. Thus, a holistic approach to education policy is expected to create an adaptive, relevant and quality-oriented education environment that prepares students to compete at the global level.